Образ мирового человека в романе Алексея Иванова „Географ глобус пропил" - Szubin, Roman (Kultury Wschodniosłowiańskie – Oblicza i Dialog, 2018)
The article is devoted to a research of archaic models in Alexei Ivanov’s creativity. On the material of the novel entitled Geographer has spent on drink the globe(Geograf globus propil) the images and motifs of rescue, as well as the archaic image of rescue described in Vardan Hayrapetyan’s hermeneutics are revealed. In the center of a research is the main character, another example of an archetype of the Russian literature — the little person. In particular, his uncommon abilities to understand, to decode and interpret are emphasized. The attention is also paid to the hermeneutical model of the communication consisting of three instances: speaking (nature), the listener (who is willfully understanding the pupil) and the interpreter (the teacher) whose efforts supplement the anthropomorphous model of unity — the all-man, the one-man (mirovoj chelovek).